Prior outpatient antibiotic use as predictor for microbial aetiology of community-acquired pneumonia: hospital-based study - van de Garde, Ewoudt MW (Springer-Verlag, 2007)
OBJECTIVE: The causative micro-organism in community-acquired pneumonia (CAP) is often difficult to predict. Different studies have examined chronic morbidity and clinical symptoms as predictors for microbial aetiology of pneumonia. The aim of our study was to assess whether prior outpatient antimicrobial treatment is predictive for determining the microbial aetiology of CAP. METHODS: This was a hospital-based prospective observational study including all patients admitted with CAP between 1 October 2004 and 1 August 2006. Microbial investigations included sputum, blood culture, sputum PCR, antigen testing and serology. Exposure to antimicrobial drugs prior to hospital admission was ascertained through community pharmacy dispensing records. Multivariate logistic regression analysis was conducted to assess whether prior outpatient antimicrobial treatment is a predictor of microbial aetiology. Patient demographics, co-morbidities and pneumonia severity were considered to be other potential predictors. RESULTS: Overall, 201 patients were included in the study. The microbial aetiology was determined in 64% of the patients. The five most prevalent pathogens were Streptococcus pneumoniae, Heamophilus influenzae, Legionella spp., Mycoplasma pneumoniae and Influenza virus A+B. Forty-seven of the patients (23%) had received initial antimicrobial treatment as outpatients. Multivariate analyses revealed that initial outpatient beta-lactam treatment was associated with a threefold increased chance of finding atypical pathogens and a threefold decreased probability of pneumococcal infection; the corresponding odds ratios were 3.51 (95% CI 1.25–9.99) and 0.30 (95% CI 0.10–0.90), respectively. Patients who received macrolides prior to hospitalisation had an increased probability of viral pneumonia. CONCLUSION: Prior outpatient antimicrobial therapy has a predictive value in the diagnostic workup aimed at identifying the causative pathogen and planning corresponding antimicrobial treatment in patients hospitalised for pneumonia.